Factors Associated with ICU Admission following Blunt Chest Trauma. (1st December 2016) - Bellone, Andrea; Bossi, Ilaria; Etteri, Massimiliano; Cantaluppi, Francesca; Pina, Paolo; Guanziroli, Massimo; Bianchi, AnnaMaria; Casazza, Giovanni
Abstract : Background . Blunt chest wall trauma accounts for over 10% of all trauma patients presenting to emergency departments worldwide. When the injury is not as severe, deciding which blunt chest wall trauma patients require a higher level of clinical input can be difficult. We hypothesized that patient factors, injury patterns, analgesia, postural condition, and positive airway pressure influence outcomes. Methods . The study population consisted of patients hospitalized with at least 3 rib fractures (RF) and at least one pulmonary contusion and/or at least one pneumothorax lower than 2 cm. Results . A total of 140 patients were retrospectively analyzed. Ten patients (7.1%) were admitted to intensive care unit (ICU) within the first 72 hours, because of deterioration of the clinical conditions and gas exchange with worsening of chest X-ray/thoracic ultrasound/chest computed tomography. On univariable analysis and multivariable analysis, obliged orthopnea (p = 0.0018 ) and the severity of trauma score (p < 0.0002 ) were associated with admission to ICU. Conclusions . Obliged orthopnea was an independent predictor of ICU admission among patients incurring non-life-threatening blunt chest wall trauma. The main therapeutic approach associated with improved outcome is the prevention of pulmonary infections due to reduced tidal volume, namely, upright postural condition and positive airway pressure.